Study of Types of Packaging Materials and Storage Temperature on The Quality of Soybean Seeds (Glycine max L. Merrill) - Ma'sumah, Ma'sumah; Moeldjani, Ida Retno; Sutini, Sutini (The University of Lampung, 2024)
The quality of soybean seeds, encompassing physical, physiological, and chemical attributes, is crucial for successful plant growth and yield. Effective seed storage is vital in maintaining seed viability, growth capacity, and adaptability, especially amid global challenges like climate change and rising food demand. This research aimed to identify the optimal packaging material and storage temperature to preserve soybean seed quality. Using a Split Plot Design with two factors and three replications, the study examined four storage temperatures (S0: 27.1°C, S1: 7-10°C, S2: 17-19°C, S3: 20-25°C) and three packaging types (K1: plastic-coated sack, K2: PE plastic, K3: aluminum foil). Results indicated that seeds stored at 27.1°C in plastic-coated sacks experienced increased moisture, reduced vigor, slower growth, lower germination, and altered protein and fat content. Conversely, PE plastic and aluminum foil packaging maintained seed quality over three months. All packaging types effectively preserved seed quality at cooler temperatures (7-25°C). This study underscores the importance of optimal storage conditions for sustainable soybean seed availability. Keywords: Packaging, Seed Quality, Soybean Seeds, Storage, Temperature.